Impacts of the COVID-19 pandemic on access to healthcare among people with disabilities: evidence from six low- and middle-income countries - Xanthe Hunt; Shaffa Hameed; Shailaja Tetali; Luong Anh Ngoc; John Ganle; Lopita Huq; Tom Shakespeare; Tracey Smythe; Zeynep Ilkkursun; Hannah Kuper; Ceren Acarturk; Nanda Kishore Kannuri; et al. (BMC, 2023)
Abstract Background The pandemic has placed considerable strain on health systems, especially in low- and middle-income countries (LMICs), leading to reductions in the availability of routine health services. Emerging evidence suggests that people with disabilities have encountered marked challenges in accessing healthcare services and supports in the context of the pandemic. Further research is needed to explore specific barriers to accessing healthcare during the pandemic, and any strategies that promoted continued access to health services in LMICs where the vast majority of people with disabilities live. Methods Qualitative in-depth interviews were conducted with persons with disabilities in Ghana, Zimbabwe, Viet Nam, Türkiye (Syrian refugees), Bangladesh, and India as part of a larger project exploring the experiences of people with disabilities during the COVID-19 pandemic and their inclusion in government response activities. Data were analysed using thematic analysis. Results This research found that people with disabilities in six countries - representing a diverse geographic spread, with different health systems and COVID-19 responses - all experienced additional difficulties accessing healthcare during the pandemic. Key barriers to accessing healthcare during the pandemic included changes in availability of services due to systems restructuring, difficulty affording care due to the economic impacts of the pandemic, fear of contracting coronavirus, and a lack of human support to enable care-seeking. Conclusion These barriers ultimately led to decreased utilisation of services which, in turn, negatively impacted their health and wellbeing. However, we also found that certain factors, including active and engaged Organisations of Persons with Disabilities (OPDs) and Non-Governmental Organizations (NGOs) played a role in reducing some of the impact of pandemic-related healthcare access barriers.